Chirality–Racemization Strategy Toward Copper (I) Iodide Hybrid Single‐Crystalline Scintillators for X‐Ray Detection and Imaging Applications. Issue 8 (15th February 2023) - Song, Zhexin; Jia, Zhenglin; Guo, Xiaoyu; Yu, Binyin; Liu, Guokui; Meng, Lingqiang; Liu, Yucheng; Lin, Qianqian; Dang, Yangyang
Abstract: Organic–inorganic hybrid copper(I)‐based halides have attracted great interest in the field of optoelectronics due to their low cost, non‐toxicity, large Stokes shift, and high photoluminescence quantum yields (PLQYs). Here, bulk zero‐dimensional (0D) organic‐inorganic hybrid copper(I)‐based (R, S‐2‐mpip)2 Cu2 I6 (mpip = methylpiperazinium, C5 H14 N2 2+ ) single crystals have been grown with equal stoichiometric ratios of R‐ and S‐2‐mpip ligands by chirality–racemization strategy for the first time. Interestingly, (R, S‐2‐mpip)2 Cu2 I6 single crystals exhibit strong blue–green photoluminescence (PL) located at 520 nm with large Stokes shift of about 230 nm and high PLQY of about 65.96%, which originates from self‐trapped excitons (STEs). More importantly, (R, S‐2‐mpip)2 Cu2 I6 single crystals also exhibit the strong radioluminescence (RL) at 520 nm, the fast X‐ray scintillation response with a light yield of about 47 000 photon MeV −1 and low detection limit of 6.48 nGyair s −1 when exposed to X‐ray irradiation condition, which is superior to that of other copper(I) iodide‐based hybrids. Based on the excellent characteristics, X‐ray imaging systems based on (R, S‐2‐mpip)2 Cu2 I6 single crystals exhibit the clear images of "QFNU" logo and crystal symbol pattern. This work not only deepens the understandings of material design and fundamental properties of these racemate systems, but also provides guidance for the further applications in the multi‐functional optoelectronics. Abstract : Bulk (R, S‐2‐mpip)2 Cu2 I6 single crystals obtained by chirality–racemization strategy exhibit the excellent scintillating characteristics with high sensitivity, fast response, high light yield value of about 47 000 photons MeV −1 and a low detection limit of 6.48 nGyair s −1 . The X‐ray images of "QFNU" logo are successfully obtained with high resolution and clarity based on the X‐ray imaging screen systems.